2021
DOI: 10.1371/journal.pone.0255163
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with unawareness of HIV-positive status in urban Ethiopia: Evidence from the Ethiopia population-based HIV impact assessment 2017-2018

Abstract: Background The HIV epidemic in Ethiopia is concentrated in urban areas. Ethiopia conducted a Population-based HIV Impact Assessment (EPHIA) in urban areas between October 2017 and April 2018 to measure the status of the country’s response to the epidemic. Methods We conducted field data collection and HIV testing in randomly selected households using the national, rapid testing algorithm with laboratory confirmation of seropositive samples using a supplemental assay. In addition to self-report on HIV diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In contrast, people with newly-diagnosed HIV did not differ in condom usage from those without HIV. Our findings corroborate those from, a populationbased impact survey in Ethiopia [26] and a systemic review and meta-analysis of studies in the United States and Canada [9] that showed an association between knowledge of HIV status and more frequent condom use. This finding points to the impact of knowing one's HIV status on sexual behaviors and explains yet another pathway by which early HIV diagnosis potentially reduces transmission.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, people with newly-diagnosed HIV did not differ in condom usage from those without HIV. Our findings corroborate those from, a populationbased impact survey in Ethiopia [26] and a systemic review and meta-analysis of studies in the United States and Canada [9] that showed an association between knowledge of HIV status and more frequent condom use. This finding points to the impact of knowing one's HIV status on sexual behaviors and explains yet another pathway by which early HIV diagnosis potentially reduces transmission.…”
Section: Plos Onesupporting
confidence: 90%
“…The number of PLWH was 196, which reflected an overall HIV prevalence of 18.5%, with the highest prevalence being observed in Kisumu City and the areas immediately to its west (Fig 1). As compared to people living without HIV (PLWOH), PLWH were more likely to be female (73.0% vs. 46.0%, p<0.001) and tended to be older (median 29 [IQR 26-31] vs. 24 [21][22][23][24][25][26][27][28] years, p<0.001). PLWH and PLWOH reported a similar total number of sexual partners in the preceding three months (median 3 [IQR 1-7] and 3 [IQR 2-6] partners, respectively, p = 0.128).…”
Section: Characteristics Of Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, factors such as knowledge about HIV/AIDS, attitudes toward testing, and perceived stigma play a crucial role in determining one's awareness of their HIV status [8,9]. Additionally, individual characteristics such as age, gender, marital status, education, and socioeconomic status may also influence awareness levels [10][11][12][13][14]. Moving beyond the individual level factors, interpersonal factors within households can significantly impact HIV-positive status awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Although chronic hepatitis B, C, and alcoholism-related CLD 17 , 18 and HIV infection 19 are common in Ethiopia, no scientific study has been conducted to evaluate the prevalence of HIV and its co-infection with HBV or HCV among CLD patients in Ethiopia. Thus, we aimed to assess the prevalence of HIV and its co-infection with HBV and HCV among CLD patients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%